2018
DOI: 10.1111/jvim.15241
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation biomarkers for evaluating oxidative stress in equine neuroaxonal dystrophy

Abstract: BackgroundEquine neuroaxonal dystrophy/equine degenerative myeloencephalopathy (eNAD/EDM) is a neurodegenerative disorder affecting genetically predisposed foals maintained on an α‐tocopherol (α‐TOH) deficient diet. Currently no antemortem diagnostic test for eNAD/EDM is available.HypothesisBecause α‐TOH deficiency is associated with increased lipid peroxidation, it was hypothesized that F2‐isoprostanes (F2IsoP), F4‐neuroprostanes (F4NP) and oxysterols derived from free radical oxidation would be increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…These are prostaglandin-like compounds released from the peroxidation of arachidonic acid, independently of the normal cyclo-oxygenase pathway, which are subsequently released for circulation by phospholipases (Griffiths and Moller, 2002; Stafforini et al, 2006; Czerska et al, 2016). The presence of isoprostanes, especially F2-isoprostane (F2-Isops), can be quantified from various biological sources, such as blood (Siti Hajar et al, 2018), urine (Roy et al, 2015), cerebrospinal fluid (Finno et al, 2018), or other fluids or tissues (Annelies et al, 2018; Finno et al, 2018; Jadoon and Malik, 2018). F2-Isops, being the most stable among the isoprostanes, is the most potent isoprostane biomarker and its level can reflect the oxidative status of vital organs, such as liver or kidneys (Morrow, 2005; Musiek et al, 2005).…”
Section: Types Of Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…These are prostaglandin-like compounds released from the peroxidation of arachidonic acid, independently of the normal cyclo-oxygenase pathway, which are subsequently released for circulation by phospholipases (Griffiths and Moller, 2002; Stafforini et al, 2006; Czerska et al, 2016). The presence of isoprostanes, especially F2-isoprostane (F2-Isops), can be quantified from various biological sources, such as blood (Siti Hajar et al, 2018), urine (Roy et al, 2015), cerebrospinal fluid (Finno et al, 2018), or other fluids or tissues (Annelies et al, 2018; Finno et al, 2018; Jadoon and Malik, 2018). F2-Isops, being the most stable among the isoprostanes, is the most potent isoprostane biomarker and its level can reflect the oxidative status of vital organs, such as liver or kidneys (Morrow, 2005; Musiek et al, 2005).…”
Section: Types Of Biomarkersmentioning
confidence: 99%
“…Interestingly, it is reported that long-term supplementation with vitamin E reduces oxidative stress in smokers, which is determined by 8-iso-PGF2α detection (Guertin et al, 2016). Isoprostanes have been evaluated as biomarkers in equine neuroaxonal dystrophy (Finno et al, 2018), Creutzfeldt-Jakob disease, Huntington's disease, Alzheimer's disease, multiple sclerosis (Jadoon and Malik, 2018), Attention-Deficit/Hyperactivity Disorder (ADHD) (Annelies et al, 2018), and in passive smokers (Siti Hajar et al, 2018).…”
Section: Types Of Biomarkersmentioning
confidence: 99%
“…Isoprostanes (IsoPs) are generated by the peroxidation of polyunsaturated fatty acids. The species F2-IsoPs are the most common, derived from arachidonic acid [ 134 ], and can be used as a mediator of oxidative stress or a nonenzymatic biomarker of endogenous lipid peroxidation [ 135 , 136 ]. Elevated concentrations of IsoPs were detected in serum, synovial fluid, and synovial membrane biopsy in patients with KOA or meniscal and cruciate ligament lesions [ 137 ].…”
Section: Markers Of Oxidative Stress In Older Adults With Koamentioning
confidence: 99%
“…Elevated concentrations of IsoPs were detected in serum, synovial fluid, and synovial membrane biopsy in patients with KOA or meniscal and cruciate ligament lesions [ 137 ]. The determinations could be performed from plasma, saliva [ 138 ], cerebrospinal fluid samples [ 136 ], or various tissue types, by gas chromatography-mass spectrometry (GC-MS) methods [ 138 ]. Decreased F2-IsoPs levels are associated with vitamin C administration [ 139 ] and with the consumption of antioxidant-rich fruits [ 140 ].…”
Section: Markers Of Oxidative Stress In Older Adults With Koamentioning
confidence: 99%
“…It is known that d -α-tocopherol (RRR-α-tocopherol) is the most potent, bioavailable isoform of vitE, 23 and that oxidative stress is occurring in the brainstem and spinal cord of eNAD/EDM affected horses. 4 , 35 Current research is ongoing to determine the exact cause of this oxidative injury and how vitE prevents such damage.…”
Section: Vitamin Ementioning
confidence: 99%